Realising Central Banks' Climate Ambitions Through Financial Stability Mandates - Paola D'Orazio; Lilit Popoyan (Intereconomics, 2022)
This paper discusses how financial stability governance has evolved and how central banks and financial regulators are coping with the threats posed by climate uncertainty, providing an overview of G20 countries' green central banking experiences in the past 20 years. The analysis shows that most central banks realise their climate ambitions through financial stability mandates, leaving the monetary stability mandate unaffected. Considering the debate on market neutrality, the concerns on the risk of overstretching the central banks' mandate, violation of Tinbergen's principle and threats posed to central banks' independence, the provided evidence reveals a mismatch between the observed policy practice and its theoretical underpinnings. Drawing on these findings, we argue that effective green central banking governance should be based on a synthesis between monetary and macroprudential policymaking.
Keywords: E44; E50; E58; 330